Towards Artificial Intelligence and New Technologies or Local Ties? Selected Variables Based on the Age of Respondents from a Survey on the Model of Local Government Consolidation in Ukraine - Włodyka, Ewa (PRAWO i WIĘŹ, 2026)
Democracy has produced a domino effect, growing and spreading across the planet. The local government system in Ukraine still requires not only a con tinuation and completion of administrative reforms, including, in particular, the implementation of modern technologies, but also the activation of the human factor through the development of civil society and increased awareness of civic participation at the local and regional levels. The article presents selected results of a research project carried out in 2025: “The consolidation potential of local government in Ukraine from the perspective of Ukrainian immigrants in Poland, taking into account the implementation of artificial intelligence in local public administration.” The quantitative study was conducted among a group of 400 immigrants of Ukrainian origin residing in Poland at the time of the study. A statistical analysis was performed to compare respondents by age in the context of the following research question: How will the age of potential Ukrainian re-emigrants currently residing in Poland affect the consolidation of local government reforms and the functioning of local government? Will new technologies play a role in this regard?